Reliability of TMS measurements using conventional hand-hold method with different numbers of stimuli for tibialis anterior muscle in healthy adults - Su, Bin; Jia, Yanbing; Zhang, Li; Li, Duo; Shen, Qianqian; Wang, Chun; Chen, Yating; Gao, Fanglan; Wei, Jing; Huang, Guilan; Liu, Hao; Wang, Lin (Frontiers in Neural Circuits, 2022)
Objective: The objective of this study was to determine the reliability of corticomotor excitability measurements using conventional hand-hold transcranial magnetic stimulation (TMS) method for the tibialis anterior (TA) muscle in healthy adults and the number of stimuli required for reliable assessment. Methods: Forty healthy adults participated in three repeated sessions of corticomotor excitability assessment in terms of resting motor threshold (rMT), slope of recruitment curve (RC), peak motor evoked potential amplitude (pMEP) and MEP latency using conventional TMS method. The first two sessions were conducted with a rest interval of 1 hour, and the last session was conducted 7-10 days afterwards. With the exception of rMT, the other three outcomes measure elicited with the block of first 3 to 10 stimuli were analyzed respectively. The within-day (session 1 vs. 2) and between-day (session 1 vs. 3) reliability for all four outcome measures were assessed using intraclass correlation coefficient (ICC), standard error of measurement and minimum detectable difference at 95% confidence interval. Results: Good to excellent within-day and between-day reliability was found for TMS-induced outcome measures examined using 10 stimuli (ICC ≥ 0.823), except in pMEP, which showed between-day reliability at moderate level (ICC = 0.730). The number of three stimuli was adequate to achieve minimum acceptable within-day reliability for all TMS-induced parameters and between-day reliability for MEP latency. With regard to between-day reliability of RC slope and pMEP, at least seven and nine stimuli were recommended respectively. Conclusion: Our findings indicated the high reliability of corticomotor excitability measurement by TMS with adequate number of stimuli for the TA muscle in healthy adults. This result should be interpreted with the caveats for the specific methodological choices, equipment setting and characteristics of sample in current study. Clinical Trial Registration Number: ChiCTR2100045141